2019
DOI: 10.1007/s00221-019-05528-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sevoflurane and isoflurane anesthesia on single unit and local field potentials

Abstract: Volatile general anesthetics are used commonly in adults and children, yet their mechanisms of action are complex and the changes in single unit firing and synaptic activity that underlie the broad decreases in neuronal activity induced by these drugs have not been well characterized. Capturing such changes throughout the anesthesia process is important for comparing the effects of different anesthetics and gaining a better understanding of their mechanisms of action and their impact on different brain regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…According to our previous works, the suppressing effect of propofol on vPAG-DA neurons promotes presynaptic GABA release and enhances postsynaptic GABA A receptor sensitivity. Similarly, the GABA A receptor also involved in the isoflurane-induced anesthesia 19 ; hence, we investigated the role of GABA A receptors in the vPAG to isoflurane anesthesia. Our study also found that intra-vPAG injection of gabazine delayed induction and accelerated arousal, suggesting the involvement of GABAergic projections in modulating vPAG-DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous works, the suppressing effect of propofol on vPAG-DA neurons promotes presynaptic GABA release and enhances postsynaptic GABA A receptor sensitivity. Similarly, the GABA A receptor also involved in the isoflurane-induced anesthesia 19 ; hence, we investigated the role of GABA A receptors in the vPAG to isoflurane anesthesia. Our study also found that intra-vPAG injection of gabazine delayed induction and accelerated arousal, suggesting the involvement of GABAergic projections in modulating vPAG-DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A larger concentration of a general anesthetic can greatly decrease or even completely abolish BOLD fMRI signal ( 40 ). Moreover, it seems that this effect might depend on the type of general anesthetic because, for example, the level of suppression of neuronal activity is very different under 1 MAC of sevoflurane and 1 MAC of isoflurane ( 41 ). Typically, local resting state activity of a majority of neurons is not visibly synchronized in the awake state.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, localized laser Doppler techniques can assess relative changes in cerebral blood flow to help investigate neurovascular coupling in vivo [ 178 ], and two-photon microscopy can represent neuronal structure in three dimensions with concurrent recording of both vasomotion and neuronal activity [ 179 ]. Moreover, classical recording of single neurons in vivo with implanted electrodes can also provide information about activity of both inhibitory and excitatory cells [ 180 , 181 ], and direct, localized brain tissue oxygen recordings with microelectrodes [ 23 ] can have the added benefit of evaluating oxygen dynamics which depend on GABAergic involvement in neurovascular coupling.…”
Section: Methodological Outlookmentioning
confidence: 99%